2012
DOI: 10.1007/s00726-012-1266-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of amino acids during hyposmotic adaptation in the whiteleg shrimp, Litopenaeus vannamei

Abstract: The penaeid prawn, Litopenaeus vannamei, was employed to investigate intracellular isosmotic regulation in situations where invertebrates encounter hyposmosis. Hemolymph osmolality was first analyzed to confirm osmoregulatory conditions in the experimental animals, followed by analysis of amino acids in muscle and hemolymph using high-performance liquid chromatography. Total muscle amino acid levels decreased when hemolymph osmolality was extremely low, whereas glycine and L-serine levels increased in the hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 45 publications
3
21
0
Order By: Relevance
“…Low growth of white shrimp reared at low salinity was assumed due to enormous energy demand in ion and amino acid osmolarity in body tissues for osmoregulation process. It was in line with Shinji et al (2012) who stated that white shrimp reared at salinity 3 g/L would synthesized certain amino acid (L-serine and lysine) which suspected to regulate osmoregulation process. Roy et al (2010) also presented that rearing media modification using magnesium and potassium fertilizer was further effective compared with feed modification technique in producing high growth and survival rate, and stable osmoregulation.…”
Section: Biological Parameter Of White Shrimpsupporting
confidence: 81%
“…Low growth of white shrimp reared at low salinity was assumed due to enormous energy demand in ion and amino acid osmolarity in body tissues for osmoregulation process. It was in line with Shinji et al (2012) who stated that white shrimp reared at salinity 3 g/L would synthesized certain amino acid (L-serine and lysine) which suspected to regulate osmoregulation process. Roy et al (2010) also presented that rearing media modification using magnesium and potassium fertilizer was further effective compared with feed modification technique in producing high growth and survival rate, and stable osmoregulation.…”
Section: Biological Parameter Of White Shrimpsupporting
confidence: 81%
“…The consistent depletion of serine across carbamazepine exposure concentrations indicates that serine may be a very sensitive indicator for carbamazepine exposure in D. magna. In crustaceans and other aquatic invertebrates, glycine can be metabolized to serine, and serine is used as an energy source in the Krebs cycle through conversion to pyruvate (Shinji et al, 2012). A decrease in serine and glycine may also be due to their use in the transsulfuration pathway that can be activated for oxidative stress defense against carbamazepine exposure, with serine used to convert homocysteine to cystathionine and glycine used to convert γ-glutamylcysteine to glutathione (Long et al, 2015).…”
Section: Nmr-based Metabolomics Of Carbamazepine Exposurementioning
confidence: 99%
“…Therefore, the two amino acids are considered to be important osmolytes for these invertebrates (Abe et al, 1999(Abe et al, , 2005Fujimori and Abe, 2002;Okuma and Abe, 1994). Another experiment indicated that the concentrations of total free amino acids were decreased in the muscle of Pacific white shrimp, Litopenaeus vannamei, acclimated at low salinity, whereas those of glycine and L-serine were increased in the hemolymph and were associated with a decrease in the osmotic pressure in the muscle, suggesting that tissue amino acids were released into the hemolymph to lower the osmolarity of the tissue (Shinji et al, 2012).…”
Section: Introductionmentioning
confidence: 99%